Modeling creep for a closed cylindrical shell under hydrostatic pressure - M. A. Magomedov; V. V. Kuznetsov; B. M. Yazyev; S. V. Litvinov (Вестник Дагестанского государственного технического университета: Технические науки, 2025)
Objective. The paper presents general equations of the moment theory of a shell of zero Gaussian curvature taking into account creep deformation. The problem of the stress-strain state of a shell is considered, with the boundary conditions: rigidly fixed at the base and free edge at the top. The cylinder is subject to internal hydrostatic pressure. Method. A linear non-homogeneous differential equation of the fourth order with respect to deflection is obtained. The solution is given in the MATLAB software package. The non-linear MaxwellGurevich equation is used as the equation of state between creep deformations and stresses. To determine creep deformations, a linear approximation of the first derivative with respect to time (Euler's method) was used. Result. The calculation of the shell made of secondary PVC was performed using the grid method. The method was tested. A program for calculation in the MATLAB package was developed with the possibility of varying the initial data and outputting a graph of the dependence of stress displacements on time. During creep in the shell, circumferential stresses increase by 14.7%. Conclusion. The proposed approach can be applied to the analysis of the stress-strain state and bearing capacity of a reinforced concrete shell as well. There are no restrictions on boundary conditions and the type of loading, and the beam material can be not only polymers and composites for construction purposes, but also concrete.